2017
DOI: 10.3390/ijms18020257
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Triglyceride Levels May Be Modulated by Gene Expression of IQCJ, NXPH1, PHF17 and MYB in Humans

Abstract: A genome-wide association study (GWAS) by our group identified loci associated with the plasma triglyceride (TG) response to ω-3 fatty acid (FA) supplementation in IQCJ, NXPH1, PHF17 and MYB. Our aim is to investigate potential mechanisms underlying the associations between single nucleotide polymorphisms (SNPs) in the four genes and TG levels following ω-3 FA supplementation. 208 subjects received 3 g/day of ω-3 FA (1.9–2.2 g of EPA and 1.1 g of docosahexaenoic acid (DHA)) for six weeks. Plasma TG were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Despite the clear influence of SNPs on the responsiveness of TG concentrations to n-3 FA supplementation, the exact mechanisms by which the 6 genes in GWAS-associated loci contribute to TG variation still remain unclear. We previously demonstrated that SNPs in GWAS-associated loci may exert their effect on TG concentrations by influencing gene expression via modulation of DNA methylation (20). However, most of these genes are poorly connected to lipid metabolism as detailed in our previous article (10).…”
Section: Discussionmentioning
confidence: 98%
“…Despite the clear influence of SNPs on the responsiveness of TG concentrations to n-3 FA supplementation, the exact mechanisms by which the 6 genes in GWAS-associated loci contribute to TG variation still remain unclear. We previously demonstrated that SNPs in GWAS-associated loci may exert their effect on TG concentrations by influencing gene expression via modulation of DNA methylation (20). However, most of these genes are poorly connected to lipid metabolism as detailed in our previous article (10).…”
Section: Discussionmentioning
confidence: 98%
“…Another study reported that gene expression levels of PPARA and apolipoprotein A1 ( APOA1 ) were influenced by the PPARA L162V polymorphism after the supplementation of omega-3 fatty acids [103]. Furthermore, it was found that changes in plasma triglycerides in response to omega-3 fatty acid supplementation could be modulated by the effect of polymorphisms and DNA methylation on expression levels of key genes identified by genome-wide association studies [104]. Additionally, genetic variants in genes encoding the selenoproteins glutathione peroxidase ( GPX1 ) and selenoprotein P ( SEPP ) could influence their gene expressions in response to supplementation with a selenium-rich Brazil nut, suggesting a possible role in the nutritional treatment of chronic degenerative conditions [105].…”
Section: Diet and Epigenetic Signaturesmentioning
confidence: 99%
“…A difference in the predictive capacity of the genetic risk model could have been observed between DHA and EPA if they differentially affected gene expression of TG-related genes, but further research is necessary to test this hypothesis. In previous publications by our group, we showed that the potential mechanism of genetic loci in the GRS may pass through modulation of transcript expression and DNA methylation levels [31]. LD between these SNPs and SNPs in nearby genes may explain several associations as well, and IQCJ (Table 2) may contribute to TG levels through calmodulin and its effect on calcitonin [18,32].…”
Section: Discussionmentioning
confidence: 81%